Carbon sequestration in the bio-edaphic ecosystem of National Highway-27 in Guwahati, Assam, India. Issue 9 (September 2020) - Bhattacharya, A.; Saikia, K.; Takhelmayum, M.; Sarkar, P.
Abstract: Vehicular pollution in cities is engendering the need to enhance the sequestration of CO2 through bio-edaphic factors, such as trees and soil. Hence, this pioneering study aimed to analyze the interdependencies of the bio-edaphic ecosystem during carbon sequestration on a national highway in Guwahati, Assam, India. To quantify the tree carbon stock, soil physicochemical properties, soil nutrients, bulk density, organic carbon, and soil carbon stock, trees with diameters at breast height (dbh) ≥ 2 cm and soil samples from different depths (0–15 cm, 15–30 cm, and 30–45 cm) were taken from six areas spread over 36 plots of equal size (2 × 10 m) arranged in a zig-zag manner. The studied parameters were compared among the different areas. It was found that the tree and soil carbon stock, along with soil nutrients, were greater in the Garchuk-Lokhra area (sample area-4). A significantly strong correlation was observed between the soil carbon stock and the above and below-ground biomass of trees (AGB, r = 0.865; BGB, r = 0.847), which indicated the co-dependencies of the bio-edaphic ecosystem in accumulating carbon. Peltophorum ferrugineum (Decne.) Benth is recommended for planting because it has emerged as a tolerant species and has the greatest carbon storage potential. The bio-edaphic ecosystem of the national highway is now on a carbon-friendly trajectory that follows the UNFCCC guidelines and the REDD+ (reducing emissions from deforestation and forest degradation) strategy. However further research on carbon budgeting is required. Abstract : Tree carbon stock; Soil carbon stock; REDD+ strategy; AGB; BGB; Ecology; Agricultural science; Environmental science; Earth sciences